IZI To Success: The Impact Of The Productive Zakat Empowerment Program On The Welfare Of Beneficiaries By The Indonesian Zakat Initiative (IZI) In North Sumatra - Nurul Husna; Muhammad Habibi Siregar (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The objective of this research is to understand the mechanism and assess the impact of the IZI To Success program implemented by the Indonesian Zakat Initiative (IZI) in North Sumatra on the welfare of beneficiaries. The approach used is a descriptive qualitative approach with a case study strategy. Data collection techniques for this research include observation, interviews, and literature review. The data analysis technique in this study consists of three stages: 1) Data reduction (simplification and abstraction of data), 2) Data presentation (organizing information in the form of narrative texts), and 3) Concluding. This study involved six informants from the IZI To Success program, divided into the "lapakberkah" program, catfish farming, and livestock development. The research findings indicate that the IZI To Success program brings welfare to the beneficiaries, as evidenced by the increase in their income after participating in the program. Similarly, the beneficiaries have become more self-reliant in practicing Zakat, Infak, and Sedekah (ZIS). Out of the total of six informants, five of them claimed to have become self-reliant in practicing ZIS both before and after participating in the IZI To Success program, while one informant is still not self-reliant in practicing ZIS.